Experimental Study on the Soil Conditioning Materials for EPB Shield Tunneling in Silty Sand. (17th December 2020) - Cheng, Chi-Hao; Liao, Shao-Ming; Huo, Xiao-Bo; Chen, Li-Sheng
Abstract : Earth pressure balance (EPB) shield tunneling in a silty sand stratum is frequently faced with the wear of rotary cutter disc, clogging, or even collapse of workface due to its noncohesive and discrete properties of silty sand material. Soil conditioning is an effective way to reduce the discrete and friction properties of silty sand and to increase its rheology and fluidity, thus improving the cutting performance of EPB machines. However, soil conditioning materials were generally prepared and injected based on past limited field experiences or lab tests which were far from reality. In this article, a ground suitability test system for simulating shield tunneling in a conditioned ground was specially developed and used in a series of tests to investigate the influences of key factors of soil conditioning on the shield cutting performance. In addition, a field experiment of shield tunneling in silty sand of Wuhan Metro was conducted for verification. The major findings were obtained as follows. (1) The proposed test system performed well in simulating and assessing the cutting performance of EPB shield in conditioned soils, and the test results agreed well with the field test. (2) The soil conditioning materials can significantly reduce the cutting torque of shield tunneling in silty sand by up to 60%–70%. (3) The optimal foam and slurry parameters are suggested in the paper for shield tunneling in silty sand, respectively. (4) The test results reveal that the slurry conditioning is better than the foam in decreasing the cutter torque in silty sand. To achieve the same effect of soil conditioning, the injection ratios of foam and slurry should be 45% and 10%, respectively, to achieve the torque reduction ratio of 60%. These findings can provide a practical reference for engineers to determine the best-fit conditioning materials and construction parameters in the silty sand stratum.